Introducing strain-rate dependent work material properties into the analysis of orthogonal cutting - Oxley, P. L. B. (College of Aeronautics, 1963)
An analysis is presented in which cutting speed, depth of cut and certain strain-rate dependent work material properties are taken into account. Good agreement between theory and experiment is shown over a wide range of cutting conditions.